Detecting HER2-positive circulating tumor cells in gastric cancer using a flow cytometry-based approach - Lee, Jan-Mou; Tu, Chia-Chun; Fang, Chih-Hao; Lin, Shian-Ren; Wang, Shiu-Lan; Lai, Wan-Yu; Tseng, Po-Wei; Liao, Wan-En; Huang, Li-Yun; Chao, Yee; Chen, Ming-Huang (Frontiers in Medicine, 2025)
BackgroundHER2 overexpression predicts the response to trastuzumab in gastric cancer (GC); however, assessing this overexpression requires invasive immunohistochemistry. Circulating tumor cells (CTCs) share comparable proteomic phenotypes to those of the primary tumor and represent a less invasive method for evaluating HER2 expression. Nevertheless, methods for detecting HER2 expression on CTCs still require further investigation.MethodsA flow cytometry method for detecting HER2-overexpressed CTCs was established by spiking NCI-N87 cells into blood from cancer-naive donors. The method was then applied to blood samples from 14 gastric cancer (GC) patients (4 with HER2-overexpressed tumors and 10 with HER2-wild type tumors) and 10 cancer-naive participants (CNPs), with all data analyzed using one-way ANOVA.ResultsThe gating strategy was defined as CD45−CK-7/8+CK-14/15/16/19+EpCAM+HER2+, with a cut-off value of 5 cells/mL. Using this in-house method, we detected HER2-overexpressed CTCs in 4 of 4 GC patients with HER2-overexpressed tumors (ranging from 8 to 29 cells/mL), while 10 of 10 CNPs had undetectable HER2-overexpressed CTCs. Among GC participants with HER2-wild type tumors, 7 of 10 GC participants had undetectable HER2-overexpressed CTCs, whereas 3 of 10 had detectable HER2-overexpressed CTCs. Furthermore, one participant with HER2-overexpressed CTCs detected by our in-house method received HER2-based targeted therapy and experienced an objective response and was free from disease progression to the date of article writing.ConclusionThis study introduces a noninvasive method for monitoring HER2 expression in GC, offering new insights into providing personalized treatment strategies.